2019
DOI: 10.1111/1467-8268.12406
|View full text |Cite
|
Sign up to set email alerts
|

Regional Integration and Energy Sustainability in Africa: Exploring the Challenges and Prospects for ECOWAS

Abstract: This study explores the extent to which regional integration can be a viable tool in driving energy sustainability in the Economic Community of West African States (ECOWAS) sub-region of Africa and vice versa. It examines the existing opportunities and the attendant challenges for improved firm productivity in the region through the appraisal of the ECOWAS West African Power Pool. Using three measures of energy sustainability, namely energy security, energy equity and environmental sustainability; the study pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 11 publications
0
21
0
2
Order By: Relevance
“…It is worthwhile to also emphasize that, in addition to departing from the mainstream literature on the finance-"environmental sustainability" nexus as discussed above, the focus of this study also steers clear of the two main strands of environmental sustainability literature, notably on, nexuses between economic development, energy consumption and energy pollution. The first group has focused on linkages between environmental degradation and economic growth (Layachi, 2019;Bah, Abdulwakil & Azam, 2019;Bah, Abdulwakil & Azam, 2020;Magazzino, Bekun, Etokakpan & Uzuner, 2020) while the second is concerned with nexuses between energy consumption and pollution of the environment (Wang & Dong, 2019;Adams & Nsiah, 2019;Nathaniel & Iheonu, 2019;Akinyemi, Efobi, Osabuohien & Alege, 2019;Acheampong, Adams &Boateng, 2019;Kuada & Mensah, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is worthwhile to also emphasize that, in addition to departing from the mainstream literature on the finance-"environmental sustainability" nexus as discussed above, the focus of this study also steers clear of the two main strands of environmental sustainability literature, notably on, nexuses between economic development, energy consumption and energy pollution. The first group has focused on linkages between environmental degradation and economic growth (Layachi, 2019;Bah, Abdulwakil & Azam, 2019;Bah, Abdulwakil & Azam, 2020;Magazzino, Bekun, Etokakpan & Uzuner, 2020) while the second is concerned with nexuses between energy consumption and pollution of the environment (Wang & Dong, 2019;Adams & Nsiah, 2019;Nathaniel & Iheonu, 2019;Akinyemi, Efobi, Osabuohien & Alege, 2019;Acheampong, Adams &Boateng, 2019;Kuada & Mensah, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Membership in the same REC ( rec ) is positively but not significantly related to intra‐African trade in Table 5. This revelation suggests that although the presence of RECs is likely to enhance trade relationship in a particular region, it might not do so in another, partly because of the generally low level of integration among Africa's RECs and their unbalanced stage of development (Akinyemi et al, 2019), as well as the widely existed phenomenon of ‘spaghetti bowl’ as demonstrated in Figure 1. Trade barriers, especially nontariff barriers within RECs, still largely impact bilateral trade and decrease the benefits of regional economic integration.…”
Section: Qap Regression Results and Discussionmentioning
confidence: 99%
“…Similarly, Mamat et al [28] recommended integration of regional markets to facilitate the augmentation of renewable energy into the energy-mixes of the ASEAN members. Besides, Akinyemi et al [29] showed how regional integration can be a viable tool for facilitating energy trade and ensuring energy sustainability within the Economic Community of West African States (ECOWAS) in Africa. Hence, it is evident that regional integration creates opportunities for renewable energy trade among the regionally integrated nations which, in turn, can be expected to boost the IITD as well.…”
Section: Literature Reviewmentioning
confidence: 99%